Removal of amines from wastewater using membrane separation processes - Zainal Abidin, M.U.S. (Trans Tech Publications Ltd, 2014)
Natural gas is one of the energy sources in the world. It consists of predominantly methane (CH4), ethane (C2H6), ethylene (C2H4), propane (C3H8) butane (C4H10), pentane (C5H12) and some impurities particularly hydrogen sulfide (H2S) and carbon dioxide (CO2) that need to be treated prior utilized. Amine solution such as diisopropanolamine (DIPA) is used to remove the CO2 and H2S in natural gas processing. However a small amount of amines losses in some unit operations causing amines discharged into the effluent wastewater. The objective of this study are to investigate the flux of water and permeate, and rejection of DIPA solution across reverse osmosis, nanofiltration and ultrafiltration membrane which known as AFC99, AFC40 and CA202 respectively. This paper studies the effect of cross-flow velocity on permeate flux and the effect of feed concentration on observed rejection of DIPA solution across AFC99, AFC40 and CA202 over the operating pressure. The results showed a significant role of cross-flow velocity on membrane performance from aspect flux obtained and phenomenon of concentration polarization that would increase the transport resistance of permeate flow. The highest flux can be achieved by high crossflow velocity. While for rejection study, rejection of all membranes increase with increase of pressure yet decrease with concentration. Â© 2014 Trans Tech Publications, Switzerland.